Residues 318 and 323 in capsid protein are involved in immune circumvention of the atypical epizootic infection of infectious bursal disease virus - Fan, Linjin; Wang, Yulong; Jiang, Nan; Gao, Yulong; Niu, Xinxin; Zhang, Wenying; Huang, Mengmeng; Bao, Keyan; Liu, Aijing; Wang, Suyan; Gao, Li; Li, Kai; et al. (Frontiers in Microbiology, 2022)
Recently, atypical infectious bursal disease (IBD) caused by novel variant infectious bursal disease virus (varIBDV) suddenly appeared in immunized chicken flocks in East Asia and led to serious economic losses. The epidemic varIBDV can partly circumvent the immune protection of the existing vaccines against the persistently circulating very virulent IBDV (vvIBDV), but its mechanism is unknown. This study proved that the neutralizing ability of vvIBDV antiserum to the epidemic varIBDV decreased by 67.76%, and the neutralizing titer of the epidemic varIBDV antiserum to vvIBDV decreased by 59.26%. In addition, one monoclonal antibody (MAb) 2-5C-6F had good neutralizing activity against vvIBDV but could not recognize well the epidemic varIBDV. The epitope of the MAb 2-5C-6F was identified and two mutations of G318D and D323Q of capsid protein VP2 occurred in the epidemic varIBDV compared to vvIBDV. Subsequently, the indirect immunofluorescence assay (IFA) based on serial mutants of VP2 protein verified that residues 318 and 323 mutation influenced the recognition of the epidemic varIBDV and vvIBDV by MAb 2-5C-6F, which was further confirmed by the serial rescued mutated virus. The following cross-neutralizing assay directed by MAb showed residues 318 and 323 mutations also affected the neutralization of the virus. Further data also showed that the mutations of residues 318 and 323 of VP2 significantly affected the neutralization of IBDV by antiserum, which might be deeply involved in the immune circumvention of the epidemic varIBDV in the vaccinated flock. This study is significant for the comprehensive prevention and control of the emerging varIBDV.